A novel index to quantify agrobiodiversity in a biocultural perspective: the case of shifting cultivation gardens in Vanuatu (Pacific). Issue 3 (15th March 2016) - Blanco, Julien; Vandenbroucke, Henri; Carrière, Stéphanie M.
ABSTRACT: Shifting cultivation is the most widespread agroforestry system in the tropics that may contribute to biodiversity conservation under certain conditions. Despite their common use, traditional biodiversity indexes prove ill-suited for assessing complex systems of this type. This study proposes a novel index, AGB, to assess agrobiodiversity in systems that mix species, varieties, lifeforms, and uses. The AGB index was tested using agrobiodiversity inventories in Vanuatu, where we compared agrobiodiversity levels and patterns of change over the course of a crop cycle between different field types. The 297 sampled fields contained a total of 127 species with an average of 10.1 species and of 11.6 varieties per field. During the cropping cycle, species and varietal richness diminish. The AGB index was compared with the Shannon and Pielou indexes and proved to be accurate for assessing and monitoring agrobiodiversity at the species and varietal levels. It may be a useful tool for agrobiodiversity monitoring in agricultural systems undergoing changes in practices and for achieving a better understanding of their biocultural resilience.